The impact of self-esteem, family and peer cohesion on social appearance anxiety in adolescence: examination of the mediating role of coping. Issue 1 (31st December 2020) - Antonietti, Chiara; Camerini, Anne-Linda; Marciano, Laura
ABSTRACT: The aim of the present study was to investigate the longitudinal relationships between self-esteem, family and peer cohesion, and social appearance anxiety (SAA) by considering the mediating role of adaptive (e.g., problem-solving) and maladaptive (e.g., rumination) coping strategies and the moderating role of gender. Data were collected via self-administered questionnaires in 2018 and 2019 in a sample of 1085 adolescents. Applying Structural Equation Modelling, results showed that self-esteem acted as a protective factor of SAA over one year. The effect was partially mediated by decreased levels of maladaptive coping strategies, while adaptive coping strategies had no effect. Perceived cohesion with family and peers had neither a the role of social support beyond perceived cohesion as well as emotion-focused adaptive coping strategies in predicting SAA.